Leveraging Organizational Structure to Achieve Ambidexterity as a Dynamic Capability in Service Organizations - Friedrich, Bennet (My University, 2023)
This thesis investigates how service firms can achieve organizational ambidexterity as a dynamic capability for sustained competitive advantage. Through 7 semi-structured expert interviews in the German real estate industry, key characteristics of the service sector influencing ambidexterity are identified, along with factors shaping organizational structure. These factors are grouped into organizational, individual, project and process, as well as external factors. Three main Models are presented. First, for the overall mechanisms and interaction of strategy, organizational ambidexterity, dynamic capabilities, and innovation, leading to a sustained competitive advantage. Second, for the mechanisms of characteristics of service firms and factors that influence organizational structure leading to a sustained competitive advantage, and third for a hybrid form of organizational structure to achieve organizational ambidexterity. Those findings contribute theoretical insights, offering a nuanced view of ambidexterity for service firms while providing a foundation for future research in related fields. Practical implications guide service firm managers and managers in real estate. Overall, the thesis unveils comprehensive models and insights to navigate the balance between exploitation and exploration in the dynamic service sector.

Diese Arbeit untersucht, wie Dienstleistungsunternehmen organisatorische Ambidextrie als dynamische Fähigkeit für einen nachhaltigen Wettbewerbsvorteil erreichen können. Anhand von 7 semi-strukturierten Experteninterviews in der deutschen Wohnungswirtschaft werden zentrale Merkmale des Dienstleistungssektors, die Ambidextrie beeinflussen, sowie Faktoren, die die Organisationsstruktur beeinflussen, identifiziert. Diese Faktoren werden in Organisations-, Individuelle-, Projekt- und Prozess- sowie externe Faktoren eingeteilt. Es werden drei Modelle vorgestellt. Erstens für die allgemeinen Mechanismen und die Interaktion von Strategie, organisationaler Ambidextrie, dynamischen Fähigkeiten und Innovation, die zu einem nachhaltigen Wettbewerbsvorteil führen. Zweitens für die Mechanismen der Merkmale von Dienstleistungsunternehmen und Faktoren, die die Organisationsstruktur beeinflussen und zu einem nachhaltigen Wettbewerbsvorteil führen, und drittens für eine hybride Form der Organisationsstruktur, um organisatorische Ambidextrie zu erreichen. Diese Ergebnisse tragen zu theoretischen Erkenntnissen bei und bieten eine differenzierte Sicht auf die Ambidextrie von Dienstleistungsunternehmen und bieten gleichzeitig eine Grundlage für künftige Forschung in verwandten Bereichen. Praktische Implikationen unterstützen die Manager von Dienstleistungsunternehmen und Unternehmen in der Wohnungswirtschaft. Insgesamt stellt die Arbeit umfassende Modelle und Erkenntnisse vor, um das Gleichgewicht zwischen Exploitation und Exploration im dynamischen Dienstleistungssektor zu gestalten.
Keywords: Organizational Ambidexterity, Dynamic capabilities, Competitive advantage, Strategy, Innovation, Organizational Structure, Service, Real Estate